Peran Customer Service Dalam Mewujudkan Pelayanan Prima Melalui Komunikasi Interpersonal Pada Nasabah Yang Mengalami Kesulitan Menggunakan Layanan Digital Bank Sumsel Babel - Gita Melinda (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze the role of customer service in delivering excellent service through interpersonal communication to customers who experience difficulties using the digital services of Bank Sumsel Babel. The digital transformation of banking offers convenience but also presents challenges for customers who are unfamiliar with technology. Customer service functions as the frontline that bridges this gap through effective, empathetic, and persuasive interpersonal communication. This research uses a qualitative descriptive method with interviews, observations, and documentation to explore customer experiences and customer service strategies. The results show that interpersonal communication plays a crucial role in building trust, explaining the steps of digital service usage, and maintaining personalized relationships despite the growing reliance on technology. These findings confirm that excellent service still requires interpersonal touch even within increasingly digitalized banking systems